An interpretative phenomenological analysis of posttraumatic growth in adults bereaved by suicide - Smith, Angela; Joseph, Stephen; das Nair, Roshan (Taylor & Francis (Routledge), 2011)
This study explored experiences of posttraumatic growth in adults bereaved by suicide. Six participants were interviewed using a semi-structured interview schedule. Transcribed interviews were analyzed from an interpretative phenomenological framework. Two superordinate themes, with three ordinate themes in each, were identified: (a) positive growth (“life view,” “knowledge of self,” and “relation to others”) and (b) social context (“gaze of others,” “public guise,” and “solace of other survivors”). Suicide survivors gain extra insights due to their experiences, but are reluctant to acknowledge that they do. This requires consideration in theoretical and clinical settings